OPTIMALISASI PENERAPAN MODEL, METODE, DAN MEDIA PEMBELAJARAN UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN MATEMATIKA DAN IPA DI SD/MI - Karomah, Nafisatul; Rafik, Ainur; Farihah, Umi; Wahyuni, Indah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study aims to analyze the effectiveness of integrating innovative learning models and instructional media in improving the quality of mathematics learning in elementary schools. The method used was a Systematic Literature Review (SLR) with a qualitative approach, through a critical synthesis of five empirical research articles published between 2024 and 2025. Data sources were obtained from accredited national journal articles discussing the application of the Student Teams Achievement Division (STAD), Contextual Teaching and Learning (CTL), Problem-Based Learning (PBL), and PAIKEM models, combined with graphic media, VIDBAR, flipbooks, and realia. The analysis results indicate that all of these pedagogical interventions had a significant impact on improving students’ learning outcomes and understanding of mathematical concepts, with a significance level of p < 0.05 and effect sizes (Cohen’s d) ranging from moderate (0.51) to very large (2.179). The most notable improvements were observed in the procedural and applicative aspects, indicating that the synergy between collaborative approaches, contextualization of material, and visual-concrete representations is effective in bridging abstract mathematical concepts with students’ empirical experiences. The study’s conclusions affirm that optimizing the integrated application of learning models, methods, and media is an evidence-based pedagogical strategy relevant to improving elementary school students’ numeracy literacy and critical thinking skills in the context of implementing the Merdeka Curriculum.